Computational formulation and immune dynamics of a multi-peptide vaccine candidate against Crimean-Congo hemorrhagic fever virus. (February 2021) - Khan, Md. Shakil Ahmed; Nain, Zulkar; Syed, Shifath Bin; Abdulla, Faruq; Moni, Mohammad Ali; Sheam, Md. Moinuddin; Karim, Mohammad Minnatul; Adhikari, Utpal Kumar
Abstract: The sole objective of this research is to devise an epitope-based vaccine candidate as prophylaxis for the Crimean-Congo hemorrhagic fever virus (CCHFV) using the knowledge of immunoinformatics and structural biology. Importantly, CCHFV outbreaks have increased in several countries resulting in increased mortality up to 40% due to the lack of prospective medication and an efficient vaccine. In this study, we have used several immunoinformatic tools and servers to anticipate potent B-cell and T-cell epitopes from the CCHFV glycoprotein with the highest antigenicity. After a comprehensive evaluation, a vaccine candidate was designed using 6 CD8 +, 3 CD4 +, and 7 B-cell epitopes with appropriate linkers. To enhance the vaccine's efficiency, we added Mycobacterium tuberculosis lipoprotein LprG (Rv1411c) to the vaccine as an adjuvant. The final construct was composed of a total of 468 amino acid residues. The epitope included in the construct showed 98% worldwide population coverage. Importantly, the construct appeared as antigenic, immunogenic, soluble, and non-allergenic in nature. To explore further, we modelled the three-dimensional (3D) structure of the constructed vaccine. Our chimeric vaccine showed stable and strong interactions for toll-like receptor 2 (TLR2) found on the cell surface. Moreover, the dynamics simulation of immune response showed elevated levels of cellular immune activity and faster clearance of antigen from the body upon repetitive exposure. Finally, the optimized codon (CAI≈1) ensured the marked translation efficiency of the vaccine protein in E. coli strain K12 bacterium followed by the insertion of construct DNA into the cloning vector pET28a (+). We believe that the designed vaccine chimera could be useful in vaccine development to fight CCHFV outbreaks. Highlights: Computational designing of multi-epitope vaccine against Crimean-Congo hemorrhagic fever virus . The chimeric vaccine was designed by joining T- and B-cell epitopes with appropriate adjuvant and linkers. The vaccine was docked onto TLR2 receptor to ensure the good binding affinity while proceeding to antigen processing. The stable vaccine-receptor interactions were evident in molecular dynamics simulation and normal mode analysis. The generated immune responses were consistent with real-life phenomena with robust immunoglobulin and cytokine activity.